2005
DOI: 10.1074/jbc.m403628200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Alzheimer's Disease-associated CLAC Protein and Identification of an Amyloid β-Peptide-binding Site

Abstract: Amyloid ␤-peptide (A␤) deposition into amyloid plaques is one of the invariant neuropathological features of Alzheimer's disease. Other proteins co-deposit with A␤ in plaques, and one recently identified amyloidassociated protein is the collagen-like Alzheimer amyloid plaque component CLAC. It is not known how CLAC deposition affects A␤ plaque genesis and the progress of the disease. Here, we studied the in vitro properties of CLAC purified from a mammalian expression system. CLAC displays features characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…Both the furin cleaved secreted (sCLAC/sCollagenXXV) and the membrane tethered (pCLAC/pCollagenXXV) forms can bind to Ab deposits. In vitro, two binding sites for Ab were identified on CLAC, one in the collagenous domain 1 and one in the non collagenous 2 domain [116,117]. It was shown that CLAC could favour the resistance of Ab aggregates to protease [118] and two studies converge to show that CLAC reduces Ab fibril growth [117,119].…”
Section: Collagens In Neural Pathologiesmentioning
confidence: 97%
“…Both the furin cleaved secreted (sCLAC/sCollagenXXV) and the membrane tethered (pCLAC/pCollagenXXV) forms can bind to Ab deposits. In vitro, two binding sites for Ab were identified on CLAC, one in the collagenous domain 1 and one in the non collagenous 2 domain [116,117]. It was shown that CLAC could favour the resistance of Ab aggregates to protease [118] and two studies converge to show that CLAC reduces Ab fibril growth [117,119].…”
Section: Collagens In Neural Pathologiesmentioning
confidence: 97%
“…This is consistent with our preliminary immunohistochemical data that ectodomain fragments of type XIII or type XXIII collagens do not appear to be associated with senile plaque amyloid. 2 Recently Soderberg et al (32) reported that another positively charged amino acid-rich domain of CLAC, LIKRRLIK, within the non-collagenous domain 2, is the major binding site for A␤ (32); they deleted or replaced these amino acid sequences with the homologous region of type XIII collagen that contains smaller number of basic amino acids compared with CLAC and found a reduced A␤ binding. This domain seemed to bind to A␤ irrespective of the triple-helix formation of CLAC because synthetic peptides mimicking these sequences were also bound to A␤.…”
Section: Discussionmentioning
confidence: 99%
“…64 Intriguingly, a nonamyloid protein found in a subset of Alzheimer's plaques was found to be a modified form of a transmembrane collagen. [65][66][67] The presence of parenchymal fibrillar collagen has been reported in human temporal lobe epilepsy. 68 Most importantly, inhibition of collagen synthesis after brain lesion prevented glial scar formation and promoted axonal regeneration and recovery of function.…”
Section: Collagen Dysregulation In Neurological Diseasementioning
confidence: 99%